A New and Alternative Route: Transvaginal Natural Orifice Transluminal Endoscopic Scarless Surgery (vaginal natural orifice transluminal endoscopic surgery) For Class 2 and Class 3 Obese Patients Suffering From Benign and Malignant Gynecologic Pathologies. (December 2022) - Kale, Ahmet; Mat, Emre; Başol, Gülfem; Gündoğdu, Elif C.; Aboalhasan, Yasmin; Yildiz, Gazi; Kuru, Betül; Kale, Ebru; Usta, Taner; Altıntaş, Mehmet; Demirhan, Recep
Background. This study was conducted to investigate the effectiveness of vaginal natural orifice transluminal endoscopic surgery (vNOTES) gynecologic scarless surgery in benign and malignant class 2 and class 3 obese patients. Materials and methods. The class 2 and class 3 obese women undergoing vNOTES scarless surgery for benign and malign indications at a tertiary referral medical center between January 2019 and April 2021 were retrospectively analyzed and surgical outcomes were measured. Results. In this study, 81 class 2 and class 3 obese patients underwent gynecological procedures using vNOTES scarless surgery. Of the 81 operations, 55 of the class 2 obese patients with benign pathologies, and 26 of the class 3 obese patients had malign pathologies. No conversion to conventional laparoscopy or even laparotomy was needed in any of the procedures. All of the surgeries were performed by the same surgeon (Prof. Dr Ahmet Kale). vNOTES scarless surgery was performed on 26 class 3 obese patients with malign pathologies. Of the 26 class 3 obese patients, 22 of the class 3 obese patients with early-stage endometrial carcinoma had very high mean body mass index 41.5 kg/m2 (range 20.6–56) and 4 of the class 3 obese patients had ascites with unknown cause and diagnosed with peritoneal carcinomatosis. The mean postoperative pain VAS scores of class 2 obese patients undergoing vNOTES scarless surgery with benign pathology at 6, 12, and 24 h were 3.19, 1.11, and .66, respectively, and the mean postoperative pain VAS scores of class 3 obese patients underwent vNOTES scarless surgery with malign pathology at 6, 12, and 24 h were 3.30, 1.76, and 1.03, respectively. Conclusion. vNOTES scarless surgery is an alternative surgical method for diagnosis and treatment not only in benign obese cases, but also in severely obese patients with early stage endometrial cancer and patients had with ascites with unknown cause. In the near future, vNOTES scarless surgery will become more preferable by experienced surgeons in benign and malignant obese cases as it has increased satisfaction with esthetic results such as less pain, and improved postoperative quality of life in the short and long term.